Fresamento de Eucalyptus grandis - Camilo, Regina de Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The process of milling wood is widely used in operations such as planing and manufacturing frames . Machines like planers , desengrossadeiras , routers , moldureiras and machining centers employ the milling process for cutting wood . In this work the process of milling CNC machining center of Eucalyptus grandis was studied because this is very much used in furniture , but without consistent studies on this process . This work a CNC machining center brand TECH Z1 for analysis of surface quality ( Ra ) in relation to the variation of cutting speed and feed in concordant and discordant tangential milling and face milling was used . We used Eucalyptus grandis . Four forward speeds ( 3, 5 , 7, and 9 m / min ) for four shear rates ( 5,9; 8,4; 10,9 and 13,4 m/s ) were used. Was used for testing a cutter finishing top speed steel with helical teeth 16mm in diameter . 6 repetitions for each test condition were performed . From the results it was observed that the best results for roughness Vc = 10,9 m / s were obtained for the milling concordant with the forward speed Vf = 7 m / min. As for Vf = 5 m / min the best finish was achieved with Vc = 8,4 m /s in discordant for milling . The feedrate and cutting influenced the roughness . The senses of concordant and discordant and cut the top and the top had a significant difference in roughness

O processo de fresamento de madeiras é muito utilizado em operações como aplainamento e fabricação de molduras. Máquinas como plainas, desengrossadeiras, tupias, moldureiras e centros de usinagem empregam o processo de fresamento para o corte da madeira. Neste trabalho foi estudado o processo de fresamento em centro de usinagem CNC de madeira de Eucalyptus grandis por ser esta uma espécie muito utilizada na fabricação de móveis, porém sem estudos consistentes relativos a este processo. Neste trabalho foi utilizado um centro de usinagem CNC da marca TECH Z1 para análise da qualidade superficial (Ra) em relação à variação da velocidade de corte e de avanço no fresamento tangencial concordante e discordante e no fresamento frontal. Utilizou-se madeira de Eucalyptus grandis. Foram utilizadas quatro velocidades de corte (5,9; 8,4; 10,9 e 13,4 m/s) e quatro velocidades de avanço (3; 5; 7; e 9 m/min). Utilizou-se para os ensaios uma fresa de acabamento de topo de aço rápido com dentes helicoidais de 16 mm de diâmetro. Foram realizadas 6 repetições para cada condição de ensaio. Com os resultados notou-se que os melhores resultados de rugosidade para Vc = 10,9 m/s foram obtidos no fresamento concordante a favor com a velocidade de avanço Vf= 7 m/min. Já para Vf = 5 m/min o melhor acabamento foi alcançado com Vc= 8,4 m/s no fresamento discordante a favor. A velocidade de avanço e de corte influenciaram na rugosidade. Os sentidos de corte concordante e frontal e discordante e frontal tiveram diferença significativa na rugosidade
Keywords: Madeira; Usinagem; Eucalipto; Trabalhos em madeira; Maquinas para trabalhos em madeira; Fresas; Maquinas-ferramenta - Controle numerico; Aspereza de superfície; Woodwork